A Systematic Literature Review and Bucher Indirect Comparison: Tildrakizumab versus Guselkumab - Kristian Garn Du Jardin; Pepi Hurtado Lopez; Mette Lange; Rachael McCool; Silvia Maeso Naval; Sandra Quickert (Journal of Health Economics and Outcomes Research)
**Background:** Psoriasis is a chronic inflammatory skin condition that impacts quality of life and requires long-term treatment and effective symptom management. Interleukin-23 (IL-23) has emerged as a key player in the pathogenesis of psoriasis and tildrakizumab and guselkumab are both immunomodulatory agents that inhibit the p19 subunit of IL-23. In its pivotal Phase III trial, tildrakizumab demonstrated greater efficacy than etanercept in moderate-to-severe psoriasis. However, there are no head-to-head trials comparing tildrakizumab with guselkumab.